2012
DOI: 10.1149/2.074302jes
|View full text |Cite
|
Sign up to set email alerts
|

Do Counter Electrodes on Metal Substrates Work with Cobalt Complex Based Electrolyte in Dye Sensitized Solar Cells?

Abstract: Yes. Testing 7 different metals as a substrate for a counter electrode in dye sensitized solar cells (DSSC) showed that some metals can be a good option for use with cobalt electrolyte. It was found that Stainless steels 304 and 321 as well as Ni and Ti suit well to the counter electrodes in DSSCs with cobalt electrolyte. In these 4 cases both the efficiency and the lifetime were similar to the reference cells on conducting glass substrates. In contrast, the cells with Al, Cu and Zn substrates suffered from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 22 publications
0
54
0
3
Order By: Relevance
“…[34][35][36] The two blue curves in Fig. 9 are otherwise identical but have a different initial concentration of iodine because the commercial electrolyte used in 34,35,36,24 Fig. 9 it is clear that the cells containing purified MPN are not less stable than the cells of Asghar et al -actually, the slopes are remarkably similar before the 85 UV 1Sun h point.…”
Section: (Ncs)(h 2 O)] [Rul 2 (Ncs)(mpn)] [Rul 2 (Ncs)(nmbi)] [Rulmentioning
confidence: 91%
“…[34][35][36] The two blue curves in Fig. 9 are otherwise identical but have a different initial concentration of iodine because the commercial electrolyte used in 34,35,36,24 Fig. 9 it is clear that the cells containing purified MPN are not less stable than the cells of Asghar et al -actually, the slopes are remarkably similar before the 85 UV 1Sun h point.…”
Section: (Ncs)(h 2 O)] [Rul 2 (Ncs)(mpn)] [Rul 2 (Ncs)(nmbi)] [Rulmentioning
confidence: 91%
“…10,12 Here the focus is not if cobalt based cells are stable or not, but does the cobalt electrolyte corrode ferritic steel or not. Previous study has shown that even cobalt complex electrolyte can corrode some metals such as copper and zinc.…”
Section: Stability Of Counter Electrode Made On Ferritic Steelmentioning
confidence: 99%
“…yellow redox couple 2,3,5,7,8 and/or results in a non-transparent corrosion product (typically very dark) that can be dispersed in the electrolyte or accumulated on the surfaces. 5,12 In the literature in the case of iodine electrolyte, the visual change of the electrolyte colour has actually been so clear that it has been used for tracking the progression of corrosion. 7 The cobalt electrolyte has a much more pale color compared to iodine electrolyte which makes the tracking of corrosion electrolyte color more difficult.…”
Section: Stability Of Counter Electrode Made On Ferritic Steelmentioning
confidence: 99%
See 2 more Smart Citations